CELLULAR AND MOLECULAR RESPONSES OF SAUDI CHRONIC MYELOID LEUKAEMIA PATIENTS TO IMATINIB (STI-571): TEN YEAR EXPERIENCE - Alenzi, Faris Q; Al-Amri, Ali M.; Alanazi, Fahad G. B.; Tamimi, Waleed; Alanazi, Ayad; Alenezy, Awwad K.; Swailmi, Farhan Al- (Journal of Ayub Medical College Abbottabad, 2012)
Background: The cyto-genetic hallmark of chronic myeloid leukaemia (CML), the Philadelphia chromosome (Ph), is the first consistent chromosomal abnormality that has been associated to a certain cancer type. In CML, Philadelphia chromosome is present leading to resistance to cell death and rapid proliferation. The aim of this study is to evaluate the different responses, toxicity and survival of Saudi CML patients to imatinib mesylate. Methods: All newly diagnosed CML patients who were treated with imatinib were included in this study. We investigated haematological, and molecular and cytogenetic responses by CBC, FISH and RT-PCR respectively. Cell proliferation and apoptosis were assayed using AUC and TUNEL respectively. Results: Of the 12 cases, 9 (75%) were males and 3 (25%) were female. Four (33%) of the cases were diagnosed incidentally and 8 cases (67%) presented mainly with fatigue (75%), fever (58%), and splenomegaly (83%). Signs of bleeding and rashes were rare at presentation. The majority of patients had low risk (8, 67%), and 33% had intermediate risk; but none of them had high risk CML. At the last follow up, 11 (92%) were in remissions. One patient (8%) was in remission after 3 years, 4 (33%) were in remission after 6 years, one was in remission after 7 years and 5 (42%) were in remission after 10 years. Only one patient had incomplete major molecular response (MMR) to imatinib after 12 years. The majority of the patients (10, 83%) were in MMR after 6 years and 42% of them were in MMR after 10 years of therapy. Adverse effects of imatinib were not reported by the patients. Imatinib treatment resulted in the reduction of proliferation and induction of apoptosis of CML CFU-GM cells. Conclusion: Imatinib mesylate is capable of treating Philadelphia chromosome-positive CP-CML without any adverse effects. Keywords: Imatinib, Philadelphia, CML, responses